MECANISMOS EN EL MERCADO DE TRABAJO EN FUNCIÓN DEL GEERO, COMO RESULTADO DE LA TEMPRANA INSEGURIDAD DEL PUESTO DE TRABAJO Y CONSECUENCIAS DE LA TRANSICIÓN A LA EDAD ADULTA - Yordanova, Gabriela; Stoilova, Rumiana (Revista Inclusiones, 2019)
The transition to adulthood is a process which poses various hardships to young people and in which they need to take significant decisions about their future life. When this process coincides with economic and financial crisis, with political and labour market transformation, the situation of the youth is further hampered. Against this background, the present article focuses on the job insecurity among the youth in Europe and investigates its consequences for the transition to adulthood. It uses information from 209 life course interviews from seven European countries (Bulgaria, the Czech Republic, Germany, Greece, Norway, Poland and the United Kingdom). The material analyses mechanisms of gendered labour market outcomes. More specifically, it discusses several situations which provoke considerable difficulties for women seeking satisfying employment, such as: motherhood (early motherhood and single mothers), care work and the need for work life balance, subjective perceptions of the interviewed on the scarring signals on the side of the employers and discrimination, based on gender and ethnicity as well as the chances for upward social mobility from a generational and gender perspective.